Decomposição e liberação de nutrientes de cobertura de braquiária em função de adubação potássica na soja - Biazatti, Renan Marré (2022)
Sandy soils have a low capacity for cation exchange, thus prone to suffer nutrients leaching processes, mainly anions, and cations such as potassium. Cover crops may reduce this problem and promote soil protection, optimizing nutrient cycling, reducing nutritional losses, which allows for greater efficiency in the use of fertilizers. Therefore, the objective of the present work was to evaluate the influence of soil cover and increasing doses of powdered fertilization on the dynamics of the Brachiaria-soybean system and on the response of potassium fertilization of the soybean crop. The experiment was installed and conducted from 2016 to 2020 at the CAD-PARECIS Experimental Station of Fundação MT, located in Campo Novo dos Parecis, MT. The experiment was carried out in a randomized block design in an incomplete factorial scheme with four replications. Main plot was constituted by the presence and absence of cover crop (brachiaria) and the subplot was constituted by the different doses of potassium applied as potassium chloride in the soybean crop (0; 60; 120; and 180 kg K 2 O ha −1 ). The results showed that the use of potassium fertilization was more efficient in the areas where soybean was cultivated following the cover crop (p < 0.05), and the maximum technical efficiency was obtained with 100 kg K 2 O ha −1 . For cultivation in absence of cover crop, a dose of 120 kg K2 O ha−1 corresponded to maximum production efficiency. Potassium fertilization applied to soybean influenced the decomposition and nutrient release of Brachiaria straw (p < 0.05), with the highest dose of soybean potassium fertilization (180kg K 2 O ha −1 ) released 160 kg K 2 O ha −1 , which was 60 % higher compared to plots cultivated without application of potassium fertilization. This confirms the potential for nutrient recovery by the cover crop and their cycling during the decomposition process of Brachiaria ruzizienses straw.